Periodic mechanical stress activates MEK1/2-ERK1/2 mitogenic signals in rat chondrocytes through Src and PLCγ1 - Ren,Kewei (2011)
The mitogenic effects of periodic mechanical stress on chondrocytes have been studied extensively but the mechanisms whereby chondrocytes sense and respond to periodic mechanical stress remain a matter of debate. We explored the signal transduction pathways of chondrocyte proliferation and matrix synthesis under periodic mechanical stress. In particular, we sought to identify the role of the MEK1/2-ERK1/2 signaling pathway in chondrocyte proliferation and matrix synthesis following cyclic physiologic mechanical compression. Under periodic mechanical stress, both rat chondrocyte proliferation and matrix synthesis were significantly increased (P < 0.05) and were associated with increases in the phosphorylation of Src, PLCγ1, MEK1/2, and ERK1/2 (P < 0.05). Pretreatment with the MEK1/2-ERK1/2 selective inhibitor, PD98059, and shRNA targeted to ERK1/2 reduced periodic mechanical stress-induced chondrocyte proliferation and matrix synthesis (P < 0.05), while the phosphorylation levels of Src-Tyr418 and PLCγ1-Tyr783 were not inhibited. Proliferation, matrix synthesis and phosphorylation of MEK1/2-Ser217/221 and ERK1/2-Thr202/Tyr204 were inhibited after pretreatment with the PLCγ1 inhibitor U73122 in chondrocytes in response to periodic mechanical stress (P < 0.05), while the phosphorylation site of Src-Tyr418 was not affected. Inhibition of Src activity with PP2 and shRNA targeted to Src abrogated chondrocyte proliferation and matrix synthesis (P < 0.05) and attenuated PLCγ1, MEK1/2 and ERK1/2 activation in chondrocytes subjected to periodic mechanical stress (P < 0.05). These findings suggest that periodic mechanical stress promotes chondrocyte proliferation and matrix synthesis in part through the Src-PLCγ1-MEK1/2-ERK1/2 signaling pathway, which links these three important signaling molecules into a mitogenic cascade.